Coastal Management Strategies to Face Climate Change and Antrophogenic Activity: A Case Study of Tamban Beach, Malang Regency, East Java (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
This research was set against the backdrop of low levels of coastal ecosystem services at the global, regional, national, and local levels. Changes in land use in coastal areas are mainly caused by an increasing intensity of climate change and irrational land use. The aim of this research was to develop coastal management strategies to deal with intensified climate change and anthropogenic processes. The methods used included using the drone approach to perform a spatial analysis, measuring the parameters of Tamban coastal waters, and applying the Partial Least Squares (PLS) method to determine community assessments and opinions about tsunami. The results of the study indicate that Tamban Beach is highly vulnerable to tsunami hazards even though the water parameters are still on the verge of pollution and that the coastal ecosystem services are not excellent. The results of this study require that the people affected by the tsunami, especially residents on Tamban beach, need to be moved to an area that is safer from the brunt of the tsunami. The area is approximately 10 kilometers from the shoreline. Besides that, this area also needs to be designated as a marine ecotourism area, but free from the tsunami disaster.